CARAWAY (Carum carvi L.) - I. T. Ushakova; V. A. Kharchenko; L. V. Bespalko; J. P. Shevchenko; E. L. Kurbakov (Овощи России)
Description information on the origin, biological features, nutritional and medical benefits of caraway has been given. Caraway Carum carvi L. is a biennial, herb plant. It is lightdemanding and winter-hardy. First year it grows a rosette of leaves, the second year it produces the flower-bearing stems and later seeds. The medicinal raw material is seeds which are picked just before the time of full maturity. The seeds content up to 20 % of proteins, 25.5 % of fatty oil, 8 % of essential oil, and vitamins, flavonoids, minerals are also present. The seeds and essential oil are used in medicine, in soap manufacture, distillery, confectionery making, bread bakery, perfumery, cosmetics products and agriculture. The caraway seeds are used in veterinary medicine to treat some disease in animals. The caraway fruit possess germicidal, antispasmodic, anesthetic, cholagogic, bileexpelling effects. The seeds can be used as diuretic, stomachic and carminative agents. The seeds of caraway increase milk production in livestock, and also are useful for human's nourishing. Usage of caraway assists to discharge sputum and mucus at lung diseases. Caraway is the excellent melliferous  plant, since the flowers bear much nectar. Production of honey can reach up to 100 kg per one hectare on average. Leaves and shoots of caraway are used in cuisine for salad recipes and to add flavor to meat and fish meal. The fleshy roots could be also consumed as root vegetable. Caraway fruits as a fragrance component are added for cucumber salting, cabbage fermentation and kvass preparation. This article presents the agricultural features for caraway cultivation in middle Russian region. The cultivar ‘Peresvet’ has been bred at VNIISSOK and included in State Register of Breeding Achievements of Russian Federation.